A Welfare Ranking of Two-Sided Market Regimes - Mats A. Bergman (Sveriges Riksbank, 2005)
Two-sided network effects in card payment systems are analysed under different market structures, e.g., competition, one-sided monopoly, bilateral monopoly and duopoly; with and without an interchange fee; for the so-called Baxters case of non-strategic merchants. A partial ranking of market structures according to their welfare effects is provided. Some support is found for the policy adopted by the EU Commission in the competition law case concerning Visas interchange fees.
Keywords: G21; L11; L44; 330; Two-sided markets; card payments; payment systems; acquiring; issuing; market structure